IDENTIFIKASI FAKTOR YANG MEMPENGARUHI SUKSES WIRAUSAHA - Saputro, Edy Purwo; Achmad, Nur; Handayani, Sih (Universitas Muhammadiyah Surakarta, 2016)
Entrepreneurship is one of essential factors that contributing for economic development. The roleÂ of women entrepreneur is pivotal in this regard. This study examined factors that influencing the successÂ of womenâs entrepreneur. This study used 231 respondents that located in Solo. The data gathered areÂ analyzed by structural equation model. The result indicated that micro, macro, performance and capabilityÂ positively influenced to the success of entrepreneur.